Targeting metabolic reprogramming in glioblastoma as a new strategy to overcome therapy resistance - D’Aprile, Simona; Denaro, Simona; Gervasi, Anna; Vicario, Nunzio; Parenti, Rosalba (Frontiers in Cell and Developmental Biology, 2025)
Glioblastoma (GBM) is one of the deadliest tumors due to its high aggressiveness and resistance to standard therapies, resulting in a dismal prognosis. This lethal tumor carries out metabolic reprogramming in order to modulate specific pathways, providing metabolites that promote GBM cells proliferation and limit the efficacy of standard treatments. Indeed, GBM remodels glucose metabolism and undergoes Warburg effect, fuelling glycolysis even when oxygen is available. Moreover, recent evidence revealed a rewiring in nucleotide, lipid and iron metabolism, resulting not only in an increased tumor growth, but also in radio- and chemo-resistance. Thus, while on the one hand metabolic reprogramming is an advantage for GBM, on the other hand it may represent an exploitable target to hamper GBM progression. Lately, a number of studies focused on drugs targeting metabolism to uncover their effects on tumor proliferation and therapy resistance, demonstrating that some of these are effective, in combination with conventional treatments, sensitizing GBM to radiotherapy and chemotherapy. However, GBM heterogeneity could lead to a plethora of metabolic alterations among subtypes, hence a metabolic treatment might be effective for proneural tumors but not for mesenchymal ones, which are more aggressive and resistant to conventional approaches. This review explores key mechanisms of GBM metabolic reprogramming and their involvement in therapy resistance, highlighting how metabolism acts as a double-edged sword for GBM, taking into account metabolic pathways that seem to offer promising treatment options for GBM.